Publicity of the Constitutional Court of the Republic of Serbia - Mitrović Igor (Trendovi u Poslovanju)
This paper deals with the problems of legal regulation of the work of the constitutional and judicial authorities in the Republic of Serbia. Given that this is the highest authoritative instance of interpretation of constitutional norms, the issue of the public is significant from the point of view of the possibility of different subjects of the statelegal order to be familiar with the results of constitutional-judicial decision-making. The knowledge of the social community with the work methodology of the Constitutional Court of Serbia ensures the expected certainty in its behavior. Any form of mystification of the functioning of this state body opens the space for manipulation and political instrumentalization of vital constitutional norms. Therefore, in providing publicity the public with constitutional and judicial work, the interest of the wider community and the state as a whole can be recognized.